Determining Factors for Readiness to Become Teachers in Economic Education Students - Dewi, Eka Rahmiana; Indrawati, Henny; Caska, Caska (Jurnal Pendidikan Indonesia, 2025)
The readiness of students to assume the role of educators remains an issue, as not all prospective teachers receive adequate support from their environment and practical experiences. This condition creates a gap between the demands of teacher professionalism and the actual preparedness of students pursuing a teaching career. The primary aim of this study is to critically analyze the factors influencing students’ readiness to become educators and to evaluate the mediating role of self-efficacy in these relationships. This research employed a quantitative approach with a survey design. The research subjects consisted of 93 economics education students who had completed teaching practice, selected using a simple random sampling technique. Data were collected using a Likert-scale questionnaire constructed from indicators of family environment, field teaching practice, professional teacher perception, self-efficacy, and teacher readiness. The instrument was tested for validity and reliability prior to data collection. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results revealed that the family environment, field teaching practice, professional teacher perception, and self-efficacy significantly and positively influence students’ readiness to become educators. These findings confirm that the synergy between internal and external factors is essential in shaping professional teacher readiness. In conclusion, teacher readiness is formed through the integration of family support, practical experiences, positive perceptions, and students’ self-efficacy.